Launch of Social Accounting Matrix + Kenya: 6th KIPPRA annual regional conference 2023 - Omune, Lensa (YouTube, 2023)
This video was recorded on June 23 2023. The launch of Social Accounting Matrix + Kenya was a side event at the 6th KIPPRA Annual Regional Conference 2023.